Bioinspired redox-driven NAD+ pump membranes with composition of annulated and cylindrical channel. (20th January 2021) - Xu, Yanglei; Tong, Yun; Yan, Fei; Chen, Sheng; Xu, Feng
Highlights: The new asymmetric nanochannel including two sections of the annulated channel and cylindrical channel is fabricated. The highly positive charged molecules NAD + transportation into membrane controlled by the redox reaction are explained. The light-controlled ion current transportation property is discussed. Abstract: In nature, ion transportation across cell membranes promotes the conduction of biological signals. Inspired by these gorgeous phenomena of nature, we construct a new artificial nanochannel membrane can well recurrence the ion transportation character of the biological ion pump by varying surface properties and present similar regulation mechanism by direct precisely controllable ion transportation. What counts is two separate channels including annulated and cylindrical channel, where the controllable translocation of ion influx across the membrane due to the change of surface charges and asymmetric structure. Notably, the mechanism of this system is that the highly positive charged molecules Nicotinamide adenine dinucleotide oxidized form cations (NAD + ) are driven to into nanochannels membrane due to the redox reaction, which is carried out by an energy-transducing oxidoreduction from its reduced form (NADH) to product its oxidized form (NAD + ) by O2 . As a light-controlled ion pump, this SiO2 membrane system can selectively restrict NADH flux. Such a new ion pump could not only provide the emergence of an in-depth mechanistic understanding on smart ion pump behavior in living organism but also promotes the development of artificial ion pump devices in power source, seawater desalination and biosensor. Graphical abstract: Image, graphical abstract